1996
DOI: 10.1073/pnas.93.17.9138
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelates bind nitric oxide and decrease mortality in an experimental model of septic shock.

Abstract: The hydroxamic acid siderophore ferrioxam- Nitric oxide (NO), a short-lived potent vasodilator, was first described as the endothelium-derived relaxation factor (EDRF) (1-3). The formation of NO from the guanidino nitrogen group of L-arginine is catalyzed by a group of enzymes termed constitutive (cNOs) and inducible (iNOs) NO synthases (3,4). The inducible form is not present constitutively in mammalian cells but is induced by proinflammatory stimuli such as bacterial lipopolysaccharide (LPS), Corynebacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Because both PA4467 and pvdL are known to be iron regulated, we confirmed that fusion I could be induced under iron-limiting conditions. We monitored fusion I ␤-galactosidase activity in medium with increasing concentrations of diethylenetriaminepentaacetic acid (DTPA), an iron-chelating agent (21). As predicted, iron limitation was sufficient to induce fusion I (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because both PA4467 and pvdL are known to be iron regulated, we confirmed that fusion I could be induced under iron-limiting conditions. We monitored fusion I ␤-galactosidase activity in medium with increasing concentrations of diethylenetriaminepentaacetic acid (DTPA), an iron-chelating agent (21). As predicted, iron limitation was sufficient to induce fusion I (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular Iron Regulates Apoptotic Cell Death by Inhibition of Caspase Activity-Hepatocytes are iron-rich compared with RAW264.7 cells, and it is known that NO readily reacts with non-heme iron to form iron-nitrosyl complexes (21,29). These complexes could, in turn, protect cells from NO-induced toxicity by either scavenging NO (29) or converting NO to a potent S-nitrosylating species (10,20).…”
Section: High Concentrations Of No Are Required For Hepaticmentioning
confidence: 99%
“…These complexes could, in turn, protect cells from NO-induced toxicity by either scavenging NO (29) or converting NO to a potent S-nitrosylating species (10,20). To determine if iron content accounted for the difference in NO sensitivity between hepatocytes and the macrophage cell line, we preloaded RAW264.7 cells with iron.…”
Section: High Concentrations Of No Are Required For Hepaticmentioning
confidence: 99%
“…Recent investigations designed to interrupt ROS formation in the context of sepsis using iron chelation strategies have met with varying degrees of success (11)(12). However, combined treatment with N-acetylcysteine (NAC), a scavenger of H 2 O 2 , and deferoxamine (DFX), an iron chelator, has not been tested, and as hypothesized by Dr. Ritter and colleagues, this combination would effectively interrupt cytotoxic ROS formation via the Fenton reaction during sepsis.…”
mentioning
confidence: 96%